TINDAK PIDANA DAN PERTANGGUNGJAWABAN PIDANA KORUPSI OLEH KORPORASI DALAM PENGADAAN TANAH UNTUK KEPENTINGAN UMUM - Joko Pranata Situmeang; Syafruddin Kalo; Edi Yunara; Mahmud Mulyadi (USU LAW JOURNAL, 2019)
ABSTRACT A business entity that may be involved in the procurement of land for public interest is clearly a legal entity/corporation in the form of a Limited Liability Company or PT. This is because PT has a very large capital. Entry of business entities in the procurement of land for public purposes clearly have a positive or negative impact. Positive impact with the involvement of corporations in the procurement of land for public interest is the acceleration of land acquisition can be faster because the funds are owned not only from the state budget (APBN/APBD) (Budget Revenue and National Expenditure/Budget Revenue and Expenditure Daera) because there are funds sourced from parties another is the corporation. Therefore, it is necessary to review the regulation of corporate participation in the procurement of land for public purposes. The elements of corruption committed by corporations in the procurement of land for public purposes and Corruption criminal liability by corporations in the procurement of land for public. Keywords: Land, Corporations and Public Interest